PELATIHAN PENGOLAHAN BAHAN LOKAL BAGI IBU PKK SEBAGAI UPAYA UNTUK MENINGKATKAN PENDAPATAN KELUARGA DI DESA TUAKEPA KECAMATAN TITEHENA - Reinaldis Masi; Mudmainna Mudmainna; Brigita Elisabet KR. Uran (LPPM Institut Pendidikan Nusantara Global, 2025)
This Community Service Program (PkM) was carried out in Tuakepa Village, Titehena District, East Flores Regency, East Nusa Tenggara, focusing on training the local women’s group (PKK) in processing banana-based local food products. Tuakepa has abundant banana resources; however, their utilization has been limited to household consumption and sales in raw form at low prices. The objective of this program was to improve the knowledge, skills, and motivation of PKK members in processing bananas into economically valuable products, such as caramel-coated chocolate banana chips. The implementation method included entrepreneurship counseling, hands-on banana processing practice, as well as reflection and group evaluation. The results indicated a positive response, with the active participation of 15 women throughout the training sessions. The products produced had distinctive flavors, were well-received by participants, and demonstrated potential as a family-based business commodity. The program’s impact extended beyond technical skill enhancement to strengthening social bonds, fostering entrepreneurial spirit, and creating opportunities for developing small-scale businesses within the PKK community. In conclusion, local food processing training has provided significant contributions to supporting family economic independence and women’s empowerment in rural areas.